The impact of Poland's EU accession on labour supply in the German-Polish border region – What can we expect? - Annekatrin Niebuhr; Silvia Stiller (European Regional Science Association (ERSA), 2004)
While barriers to trade between EU-15 and accession countries have been completely abolished on May 1st 2004, other integration impediments remain to exist in the enlarged EU. These will steadily decrease within the next years, e.g. by new member states joining the Schengen Treaty and Euro area. A significant outstanding integration step is the liberalisation of labour mobility between EU-15 and new member states which will be realised not later than 2011. In this context it is often argued that the free movement of labour could worsen labour market problems in the former EU-15, especially in regions neighbouring the new member countries. This paper provides an assessment of the impact of enlargement on labour markets in the German-Polish border region. As a starting point for the analysis, current labour market conditions and income disparities in the German-Polish border region are analysed. Furthermore, the paper summarises relevant implications of migration theories and gives an outlook on the development of factors determining cross-border labour migration in the German-Polish border region. Finally, different estimates of migration and commuting potential affecting labour markets in the German-Polish border region until 2020 are discussed.
Keywords: 330